1974
DOI: 10.1177/001872087401600511
|View full text |Cite
|
Sign up to set email alerts
|

Decision Processes of Baseball Batters

Abstract: The human performance characteristics of pitching and batting within the context of baseball game situations are examined to determine their influence o n the batter's decision to swing or not at a pitched ball. Signal detection theory techniques are used o n generated data to show how the probability of the batter swinging at a "strike" and leaving a "ball" could be optimized. Applications of this approach to game situutions and areas for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In summary, McPherson (1993) showed that the objective and subjective variables proposed to influence batting decisions (Newell, 1974) can be measured and that performers learn to access this information when representing the problem situation. Moreover, experts have the ability to adapt their problem representations to the situation at hand by using sophisticated knowledge structures.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, McPherson (1993) showed that the objective and subjective variables proposed to influence batting decisions (Newell, 1974) can be measured and that performers learn to access this information when representing the problem situation. Moreover, experts have the ability to adapt their problem representations to the situation at hand by using sophisticated knowledge structures.…”
mentioning
confidence: 99%
“…The added advantage of these mechanisms is that current event and action plan profiles are used to compensate and make adjustments during time-constrained performance. Findings in the previously reviewed baseball batting studies suggest that these knowledge structures (Gray, 2002;Newell, 1974;Paull & Glencross, 1997) develop with expertise as well as over long bouts of competition (McPherson, 1993).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the rigid and repetitive nature of baseball, Newell (1974) argued that signal detection theory may be applied to the batter's dilemma of whether or not to swing at a pitched ball. If a pitch passes through the "strike zone" the batter wants to attempt to hit it, since if he does not, it counts as a "strike" against him (three strikes and he is out).…”
Section: Baseballmentioning
confidence: 99%